2007
DOI: 10.1016/j.physletb.2007.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Jet-radius dependence of inclusive-jet cross sections in deep inelastic scattering at HERA

Abstract: Differential inclusive-jet cross sections have been measured for different jet radii in neutral current deep inelastic ep scattering for boson virtualities Q^2 > 125 GeV^2 with the ZEUS detector at HERA using an integrated luminosity of 81.7 pb^-1. Jets were identified in the Breit frame using the k_T cluster algorithm in the longitudinally inclusive mode for different values of the jet radius R. Differential cross sections are presented as functions of Q^2 and the jet transverse energy, E_T,B^jet. The depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 80 publications
4
34
0
Order By: Relevance
“…Table 8, indicates that the performance of the three jet algorithms is similar. These determinations are consistent with previous determinations in NC DIS [5][6][7] at HERA, with the results obtained in pp collisions [70] and have a precision comparable to those obtained in individual determinations from e + e − experiments [71]. These values are also con- sistent with the world average [63], as well as with the HERA 2004 average [72] and the HERA 2007 combined value [73].…”
Section: Determination Of α S (M Z )supporting
confidence: 91%
See 1 more Smart Citation
“…Table 8, indicates that the performance of the three jet algorithms is similar. These determinations are consistent with previous determinations in NC DIS [5][6][7] at HERA, with the results obtained in pp collisions [70] and have a precision comparable to those obtained in individual determinations from e + e − experiments [71]. These values are also con- sistent with the world average [63], as well as with the HERA 2004 average [72] and the HERA 2007 combined value [73].…”
Section: Determination Of α S (M Z )supporting
confidence: 91%
“…Jet cross sections provided precise determinations of the strong coupling constant, α s , and its scale dependence. The jet observables used to test pQCD included inclusive-jet [1][2][3][4][5][6][7], dijet [1,4,[6][7][8][9] and multijet [6,7,[10][11][12] cross sections in neutral current (NC) deep inelastic ep scattering (DIS), inclusive-jet [13,14], dijet [15][16][17][18][19][20] and multijet [21,22] cross sections in photoproduction and the internal structure of jets in NC [23][24][25] and charged current [26,27] DIS. These studies also demonstrated that the k T cluster algorithm [28] in the longitudinally invariant inclusive mode [29] results in the smallest uncertainties in the reconstruction of jets in ep collisions.…”
Section: Introductionmentioning
confidence: 99%
“…MC studies of the reconstruction performance and comparisons between jets on detector, hadron and parton level indicate that R 0 = 1 is a good choice for the phase space of this analysis. This is also in agreement with the result reported in [37]. The transverse component of the jet four-vector with respect to The jet axis is transformed to the laboratory rest frame, and jets with a pseudorapidity in the laboratory frame of −1.5 < η jet lab < 2.75 are selected.…”
Section: Reconstruction Of Jet Observablessupporting
confidence: 88%
“…In a recent summary and combination [63] of precision measurements at HERA, values of α s where determined from fits of NLO QCD predictions to data of inclusive jet cross sections in neutral current deep inelastic scattering at high Q 2 [64][65][66]. The overall combined result,…”
Section: α S From Jet Production In Deep Inelastic Scattering Processesmentioning
confidence: 99%